Influence of Eco-Culture on Urban Development - Zhou, Xiaocui; Chang, Yanju (Journal of Environmental Accounting and Management, 2026)
Eco-culture is essentially a social ideology which promotes coexistence and mutual prosperity between mankind and nature, in order to realize cohesive and harmonious development of ecology, economy and society. Based on the analysis of essence ofeco-culture, this paper reveals a mechanism that eco-culture influenced on urban development and analyzes its phenomena. We find that eco-culture is the driving force and soul of urban ecological development, which has penetrated into every aspect of urban society, economy, planning and construction. Eco-culture can not only contribute to resolve ecological crisis, but also facilitate the resource-saving and environment-friendly society development, also promotes the circular economy development, and plays an important role in constructing ecological physical space.